Combining Epigenetic and Immunotherapy in Cancer: Molecular Mechanisms - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Immunotherapy, particularly the idea of immune checkpoint blockage is currently draw much attention in cancer treatment. It has been approved as an adjuvant, however, it cannot be a single cancer treatment.CONTENT: The discovery of the basic ligand-receptor interactions between immune and cancer cells inside the tumor microenvironment has led to the current interest in immunotherapy, specifically immune checkpoint inhibition. Different ligands produced by cancer cells interact with immune cells' surface receptors, activating inhibitory pathways, such programmed cell death protein 1 (PD-1)/programmed cell death ligand 1 (PD-L1), that cause immune cells to become immunologically tolerant. On the other side, epigenetic modulators also play a critical role in enhancing the tumor microenvironment and regaining immunological recognition and immunogenicity. Some findings showed that such immune suppression can be reversed through various mechanisms involving antigens pathways, immune genetic, and epigenetic pathways. These findings have created a very encouraging foundation for research on the combination of epigenetic and immunotherapeutic drugs as cancer treatments.SUMMARY: The effectiveness of this suggested paradigm can only be demonstrated by clinical studies. Epigenetic treatment might replace immune checkpoint therapy as a powerful new cancer care technique that is generally well tolerated and should be proven with adequate clinical trials.KEYWORDS: epigenetics, immunotherapy, PTM, DNMT, HDAC, immune check point